Nas tramas da justiça: sociabilidades e resistências de escravizados na Uberaba oitocentista - Muniz, Flávio Junio Neres (2020)
The objective of this research is to understand the socio-political conditions that made it possible that an enslaved woman could bring justice against her landlords, for the aggressions inflicted on her daughter, in the Uberaba District, in the Province of Minas Gerais at nineteenth century. The main source used was the criminal case that deals with aggressions against Alexandrina, which ran from 1881 to 1882. Were used also information and data collected from various supplementary sources such as Minutes of Chamber and associations, inventories, baptism and marriage records, as well as period newspapers. In addition to content analysis, the proposal was based on the methodology analysis of sociability networks seeking to understand the dynamics of actions, their extension and articulation in the protagonism of the enslaved as subjects of law acting in the intricacies of Brazilian justice, in the twilight of the slave system in the XIX century. Although article 75 of the 1841 Criminal Procedure Code establish that the slave's denunciations against the master would not be admitted, the analysis of the process made it possible to perceive the way enslaved subjects operated within its margins of maneuver in the fight for freedom, rights and justice. The interdiction of the actions of enslaved people did not mean the impossibility of exercising freedom and the practice of resistance be it in the private sphere, in everyday relationships and even in the legal sphere. It was noticed that the actions of the enslaved when searching for justice, were immersed in sociability between enslaved and freed, as well as as in local political plots that made up a framework where struggles and resistances of these subjects were instituted.